Conceptual Study of Tube Launched Unmanned Aerial Vehicle (UAV) - George, Raji; K. Vinita Babu; Adhish Palyam Venkatesh; T Ananda Mukesh; Rakesh Kumar; Prem Ranjan (Journal of Mines, Metals and Fuels, 2023)
Unmanned Aerial Vehicle Technology is used in the field of the military as well as in the commercial domain. Current paper deals with Tube Launched UAV, wherein the complete UAV must fit inside a cylindrical tube and launch from the tube in a very short time. Mainly mechanical design and analysis are carried out towards wing folding for fitting the folded UAV inside a tube of 6 inch diameter. In addition, Propulsion system sizing, catapult launch system design including comparative study of different ramp angles for launching the tube with encapsulated UAV is also highlighted. The main objective behind using Tube Launched Unmanned Aerial Vehicles is that they can be transported in compact spaces like tubes that can be carried in ships, helicopters, planes, and larger drones